2010
DOI: 10.1016/s1672-0229(10)60011-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Survey and Evolutionary Analysis of Trypsin Proteases in Apicomplexan Parasites

Abstract: Apicomplexa are an extremely diverse group of unicellular organisms that infect humans and other animals. Despite the great advances in combating infectious diseases over the past century, these parasites still have a tremendous social and economic burden on human societies, particularly in tropical and subtropical regions of the world. Proteases from apicomplexa have been characterized at the molecular and cellular levels, and central roles have been proposed for proteases in diverse processes. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In addition, two PDZ domains are present in the C-terminal end of the protein. According to this modular architecture combining a protease domain with one or more C-terminal PDZ domains characteristic of Deg-like serine proteases, this protein was named Tg DegP [ 15 ]. Tg DegP harbors a predicted signal peptidase cleavage site after Ala30, indicative of trafficking along the secretory pathway.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, two PDZ domains are present in the C-terminal end of the protein. According to this modular architecture combining a protease domain with one or more C-terminal PDZ domains characteristic of Deg-like serine proteases, this protein was named Tg DegP [ 15 ]. Tg DegP harbors a predicted signal peptidase cleavage site after Ala30, indicative of trafficking along the secretory pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Genome mining and multiple sequence alignment identified homologs of Tg DegP in most Apicomplexa, including Eimeria , Neospora , Hammondia , Babesia , Theileria and Plasmodium spp . with the notable exception of rodent malaria parasites [ 15 ]. Multiple copies of trypsin genes have been found in Toxoplasm a and Plasmodium .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same year, Gaskell et al ., identified secreted enzymes in Toxoplasma gondii using SHARKhunt which used profile HMM based on the PRIAM polypeptide profile library to search for a set of genomic DNA sequences potentially encoding such proteins [12] . In 2010, Arena et al , identified 16 new genes encoding trypsin proteases in 8 Apicomplexan genomes [13] . Ghouila et al , constructed a system for identifying protein domains based on comparing HMM and Pfam profiles so that a Pfam family was represented by a multiple sequence alignment and a profile HMM [14] .…”
Section: Introductionmentioning
confidence: 99%